Farm households' risk perception, attitude and adaptation strategies in dealing with climate change: Promise and perils from rural Pakistan. (February 2020) - Khan, Imran; Lei, Hongdou; Shah, Irshad Ali; Ali, Imad; Khan, Inayat; Muhammad, Ihsan; Huo, Xuexi; Javed, Tehseen
Highlights: Pakistan is highly vulnerable and exposed to extreme climatic events. Farmers' risk perception and attitude are crucial factors influencing farm-related decisions. Majority of the farmers were aware of climate change. The farmers adapted several adaptation measures to cope with climate change. Several factors, including poverty and credit constraints, make farmers more vulnerable. Abstract: Pakistan is highly vulnerable to extreme climatic events, such as floods and droughts. This study determines the farmers' risk perception, risk attitude, adaptation measures and various aspects of vulnerability to climate change (e.g. floods, droughts, heavy rainfalls, pests and disease) at farm level in rural Pakistan. The risk perception and attitude of farm households are crucial factors that influence farm productivity, investment and management decisions at this level. A well-designed questionnaire was used to interview 720 farm households from six districts of the Khyber Pakhtunkhwa province. A binary logit model was used to determine the main factors that affect the choice of adaptation strategies of the farm household. The findings revealed that crop diversification, changing crop varieties, altering the crop calendar, varying the fertilizer used, mulching and farm insurance were the main adaptation strategies followed by farm households. The results of the binary logit model revealed that age, education, farm size, household size, credit accessibility, annual income and the perception on the increase in temperature and decrease in rainfall had significant influence on the selection of the adaption strategies. The findings of this study can provide guidance, policy recommendations and reference for future researchers.